Energy value of unfermented dried grape pomace as substitute of alfalfa hay in diets for growing lambs - Calderón-Cortés, José F.; González-Vizcarra, Víctor M.; Pétriz-Celaya, Yuridia; Pujol, Lourdes C.; Barreras, Alberto; Plascencia, Alejandro (Austral Journal of Veterinary Sciences, 2018)
The energy value of unfermented dried grape pomace (DGP) was evaluated in an 84 d feeding trial on 16 Pelibuey×Dorper lambs (17.8 ± 2.0 kg). The control diet contained 90% mature alfalfa hay and 10% concentrates. Treatments consisted in the replacement (DM basis) of alfalfa hay by DGP at 0, 10, 20 or 30%. Lambs were blocked by weight and assigned individually to pens. Increasing DGP level in diet tended (P=0.06) to decrease daily gain and linearly increased (P=0.04) dry matter intake (DMI); thus, feed efficiency, dietary energy, and observed-to-expected diet NE were linearly decreased (P<0.01), increasing linearly (P<0.01) observed-to-expected DMI coefficient as DGP level was increased in the diet. There were no effects of treatments on carcass characteristics. Using the replacement technique, the energy value of DGP were 0.80, 0.75 and 0.67 Mcal ENm/kg DM, for 10, 20 and 30% of inclusion, respectively. It is concluded that the estimated NE of DGP at 10% inclusion level in the diet is very similar to the NE value assigned by the NRC (2007) for the fermented DGP. Increasing the inclusion of DGP levels beyond 10% decreases its energy value, maybe due to the negative associative effects of chemical compounds (such as phenols) naturally contained in DGP.